Morbidity Cost and Willingness to Pay for Healthcare Insurance among Wheat Farmers in Jigawa State of Nigeria - Mohammed Sanusi Sadiq; Muhammad Ahmad; Emmanuel Gama; Abbas Sambo (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The study determined the costs of morbidity and farmers' willingness to pay for health insurance in the Jigawa State of Nigeria using a cross-sectional data collected from 284 farmers through a multi-stage sampling technique. Using an easy-route cost approach, a well-structured questionnaire coupled with interview schedule was used for data collection. Besides, the collected data was then analysed using both descriptive and inferential statistics. Empirically, the majority of farmers utilised an accumulation strategy for livelihood sustenance, alongside enterprise diversification – which acted as a catalyst in increasing their stocks and consumption outcomes, thus smoothing their income and consumption. However, financial and, at worst, physical livelihood capitals posed challenges that affected farmers' livelihood assets in the study area. Furthermore, malaria emerged as the major health issue affecting livelihoods; consequently, slightly over half of the sampled population agreed to the notion of a social health insurance scheme for a healthy livelihood. However, this inclination was largely influenced by the overlooked or nearly neglected social learning aspect of extension service delivery. Therefore, as a method to reduce public capital expenditure on healthcare for livelihoods in the study area, the study recommends that policymakers expand the healthcare scheme to include the farming community, going beyond formal organisations, thereby enhancing farm family livelihoods specifically and overall economic growth and development in general. Nonetheless, enhance institutional factors, alongside social extension, financial and infrastructural facilities are recommended.